Inside Back Cover: Volume 2 Issue 4. (22nd December 2021) - Meng, Xiangyu; Qiu, Lin; Xi, Guangcheng; Wang, Xiaotian; Guo, Lin
Abstract : Inside back cover image : Surface enhanced Raman scattering (SERS) spectroscopy is an excellent analytical tool for the identification and characterization of molecular species. A lot of efforts have been made by researchers to design high‐performance SERS substrates including tuning the localized surface plasmon resonance (LSPR) position, assembling of nanoparticles, defect engineering and doping strategy. This review summarized the recent developments of noble metal and semiconductor substrates, and then proposed the key factors for substrate design and future directions, which presents a comprehensive overview to researchers and promote research activities of SERS‐active materials. (DOI: https://doi.org/10.1002/smm2.1058 )